Big Potential From Silicon-Based Porous Nanomaterials: In Field of Energy Storage and Sensors - Manj, Rana Zafar Abbas; Chen, Xinqi; Rehman, Waheed Ur; Zhu, Guanjia; Luo, Wei; Yang, Jianping (Frontiers in Chemistry, 2018)
Silicon nanoparticles (SiNPs) are the promising materials in the various applications due to their unique properties like large surface area, biocompatibility, stability, excellent optical and electrical properties. Surface, optical and electrical properties are highly dependent on particle size, doping of different materials and so on. Porous structures in silicon nanomaterials not only improve the specific surface area, adsorption, and photoluminescence efficiency but also provide numbers of voids as well as the high surface to volume ratio and enhance the adsorption ability. In this review, we focus on the significance of porous silicon/mesoporous silicon nanoparticles (pSiNPs/mSiNPs) in the applications of energy storage, sensors and bioscience. Silicon as anode material in the lithium-ion batteries (LIBs) faces a huge change in volume during charging/discharging which leads to cracking, electrical contact loss and unstable solid electrolyte interphase. To overcome challenges of Si anode in the LIBs, mSiNPs are the promising candidates with different structures and coating of different materials to enhance electrochemical properties. On the basis of optical properties with tunable wavelength, pSiNPs are catching good results in biosensors and gas sensors. The mSiNPs with different structures and modified surfaces are playing an important role in the detection of biomarkers, drug delivery and diagnosis of cancer and tumors.